PERAN ISTRI SEBAGAI PENCARI NAFKAH UTAMA PERSPEKTIF MUBAADALAH DAN UNDANG-UNDANG NO. 1 TAHUN 1974 - Syafaatin Fransiska Yuliandra; Dwi Ari Kurniawati; Syamsu Madyan (Jurnal Hikmatina, 2020)
AbstractA living is an obligation that is born as a result of a legal marriage relationship. This obligation is required for men to their wives and families. However, what if it is done by women seeing in the current modern era changes in the way of society's view of the role and position of women in society, the large number of women who have a career, modern life that does not limit the movement of women, including wives who make a living. The existence of this phenomenon requires a more in-depth study of the relationship between husband and wife who actually must be confused. The problems that are the focus of the research according to the background are: 1. What is the role of the wife as the main breadwinner from the perspective of Mubaadalah; 2. What is the role of the wife as the main breadwinner perspective of Law No. 1 of 1974 concerning Marriage. This study uses a normative juridical approach and reciprocal interpretation methods (understand mubaadalah). This type of research uses a research library whose data can be obtained from books or variables that are relevant to the writing. The conclusion of this research is according to two perspectives. According to the concept of mubaadalah, the position between man and woman or husband and wife is mubaadalah (oversight). According to the Marriage Law that the rights and positions of husband and wife are balanced. So, it does not matter if the wife acts as a breadwinner. However, this is inseparable from a number of provisions when the wife decides to become a breadwinner in the family. Namely, it still does not leave its domestic role and there is an agreement between herself and her husband. Kata Kunci : wife’s role, breadwinner, mubaadalah, marriage law